Introduction to strategies for organic synthesis - Starkey, Laurie S. (Hoboken, New Jersey : Wiley, 2012)
"Providing advanced undergraduates and graduate students with a stepping stone from beginning level Organic Chemistry courses to organic synthesis research and/or graduate level coursework, Introduction to the Strategies of Organic Synthesis teaches the practical skills of making logical retrosynthetic disconnections, while reviewing basic organic transformations, reactions, and reactivities. The book is written to help undergraduates feel comfortable performing retrosynthetic analysis of a target molecule and subsequently develop more secure understanding of organic chemistry reactions overall"-- Provided by publisher."This book helps readers feel comfortable performing retrosynthetic analyses of target molecule synthesis and they will have a more secure understanding of organic chemistry reactions overall"-- Provided by publisher.